Ileocecal Intussusception Due to Appendiceal Mucinous Neoplasm: A Case of Diagnostic Anticipation and Management Perspective - Maria João Vale; Pedro Caldes; Sónia Bispo; Augusto Lourenço (Medicine and Medical Research: New Perspectives Vol. 4, 2024)
Introduction: The intussusception is a rare cause of intestinal occlusion in adults (1-5%). Usually, they are secondary to an underlying pathology, generally identified intraoperatively. Mucinous appendiceal neoplasm occurs in less than 1% of appendicectomies. This work aims to present an unusual case and our therapeutic approach. Presentation of Case: A 54-year-old female patient came to the emergency department with abdominal pain. Complementary diagnostic exams showed an image of ileocolic invagination due to an appendicular mass, confirmed intraoperatively. A right hemicolectomy was performed for oncological purposes. The anatomopathological study revealed a low-grade appendicular mucinous neoplasm. Discussion and Conclusion: The treatment of ileocolic invagination is surgical, due to the high incidence of a malignant etiology. In this particular case, there was already a preoperative suspicion of an appendicular neoplasm, which justified proposing a right hemicolectomy. There is no consensus on the post-operative monitoring of Low-Grade Appendiceal Mucinous Neoplasm (LAMN). After 5 years, the patient was asymptomatic, with no signs of recurrence.